Penatalaksanaan Fisioterapi Pada Plexus Brachialis Injury Sinistra Di RS Orthopedi Prof Dr Soeharso - Sandi Putra, Nico, Sugiono, S.Fis, MH.Kes (2015)
Background: Plexus BrachalisInjury an injury or trauma that occurs in brachial plexus due to hit, shot or stabbed, and a strong pull spontaneously on the arm or neck, causing disconnected, pinched nerve or nerve root avulsion even the brachial plexus. In the case of plexus brachial injury injured arm will bedegenerated in muscle strength and decreased sensation, so functional activity at the forearm will be decrease. Objective: To investigate the implementation of Physiotherapy in improving muscle strength and range of motion in the case of the plexus brachial ijury with modalities Electrical Stimulation and Therapeutic Exercise Results: After treatment for 6 times gained muscle strength assessment in sholder Flexor T1: 2, still T6: 2, abductor sholder T1: 2, still T6: 2, Flexor elbow T1: 3, became T6: 4, Palmar flexor wrist T1: 3, became T6: 3+, extensor fingers T1: 3, became T6: 4, range of motion left sholder still no increase, S: T1: 0-0-0, becoming T6: 0-0- 0, F: T1: 0-0-0, becoming T6: 0-0-0, T: T1: 0-0-0, becoming T6: 0-0-0. Daily functional activities increased from T1 score: 55 to T6: 57. Conclusion: Electrical stimulation can increase muscle strength of the left arm on the condition of the brachial Plexus Injury, exercise therapy can improve muscle strength of the left arm on the condition of the brachial plexus injury, but there has been no improvement in muscle strength driving left sholder and there has been no increase in range of motion in the left sholder, an increase in daily functional activities.